Application of chain management of intravenous access in surgical patients (围手术期静脉通路链式管理方案在外科手术患者中的应用效果) - YUAN Yuan (袁媛); ZHAO Yuhuan (赵玉焕) (中西医结合护理)
Objective To evaluate the application effect of chain management of intravenous access in surgical patients. Methods Totally 258 patients undergoing surgical treatment between January and May 2021 were included as the control group. Another 257 patients undergoing surgical treatment between January and May 2022 were included as the observation group. The control group received routine management of perioperative check on intravenous access, and a chain management model was adopted in the perioperative check on intravenous access. The number of indwelling needle used was recorded. The indwelling needle retention time, venipuncture-associated cost, nursing cost and failure rate of indwelling needle were compared between two groups. Results The total number of indwelling needle used was 339 in the control group, and was 272 in the observation group. There was no significant difference in indwelling needle retention time between two groups (P＞0. 05). The venipuncture-associated cost and nursing-associated cost in the observation group were lower than those in the control group (P＜0. 01). The failure rate of indwelling needle was 5. 42%(14/272) in the observation group, which was lower than 31. 49%(81/339) in the control group (P＜0. 05). Conclusion The chain management of intravenous access helps to reduce the medical cost of patient and failure rate of indwelling needle during operation period. (目的 探讨围手术期静脉通路链式管理方案在外科手术患者中的应用效果。方法 选取2021年1月—5月德阳市第二人民医院收治的258例手术患者为对照组, 选取2022年1月—5月收治的257例手术患者为观察组。对照组采用静脉通路常规护理, 观察组采用静脉通路链式管理方案。观察两组各穿刺部位留置针使用数量, 比较两组留置针留置时间、静脉穿刺耗材费用、护理费用以及留置针失效率。结果 对照组留置针使用总数量为339枚, 观察组为272枚。两组留置针留置时间比较, 差异无统计学意义(P＞0. 05)。观察组静脉穿刺耗材费用以及护理费用均低于对照组, 差异有统计学(P＜0. 01)。观察组留置针失效率5. 42%(14/272), 低于对照组的31. 49%(81/339), 差异有统计学意义(P＜0. 05)。结论 静脉通路链式管理方案应用于外科围手术期患者能有效减少医疗费用, 降低留置针失效率。)